The Shift in the Teacher's Role in Digital-Based Laboratory Sessions: The Transition from Demonstrator to Learning Facilitator - Miptahul Jannah; Muhamad Rizqy; Bayu Hadiatma Fasya (Indonesian Publication Center, 2025)
The development of digital technology has brought changes to the learning process, including practical activities. Practicals, which previously focused on teacher demonstrations, are now shifting to more interactive learning utilizing digital technology. This article aims to examine the shift in the teacher's role in digital-based practicals, from demonstrator to learning facilitator. The method used is a literature review, examining various relevant scientific sources. The results of the study indicate that the use of digital technology in practicals can increase student engagement, independence, and understanding. In this case, the teacher acts as a guide who facilitates students' exploratory learning process.